ACHIEVEMENTS AND DISADVANTAGES OF USING INTERACTIVE TECHNIQUES IN LESSONS - Boltaboeva Umida Raxmonovna; Mahmudova Dilnoza Munavarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the use of interactive techniques in the lessons expressed an opinion on the achievements and disadvantages of the effectiveness of interactive techniques, as well as the use of interactive methods in the course of the lesson.